CONSTITUTIONAL LEGITIMACY: SHARIA LAW, SECULARISM AND THE SOCIAL COMPACT - Akhtar, Zia (UI Scholars Hub, 2011)
This article considers the general points relating to the application of Sharia law which challenges legislators in the political instability of a number of Middle Eastern countries. The question explored is how governments of these countries who are facing discontent can work towards constitutional governance. As an example comparison is made between the Islamic Republic of Pakistan and Indonesia with the largest Muslim populations. In Pakistan an inherited Westminster Parliamentary system with a common law codified dated at the time of the British rule is supplemented by criminal penalties as present in the Hudood ordinances. These codes enforce punishments for some crimes and these were promulgated in the early 1980s during the reign of the Pakistani conservative military government. These different layers of jurisprudence do not accord with a uniform legal precedence and creates a clash between liberals and the fundamentalists who want an all pervasive Sharia law . The Pakistani legal canon of Islamic law has been restricted by the secular ideology of the state which has parallels in other Asian countries with a Muslim majority. However, there is an issue of compatibility of a secular ideology and the application of Sharia. It needs an exposition of thought that takes account of the enlightenment in Europe which led to the social contract theory in the 18th century. This theory rejects the narrow interpretation of divine authority and presents the jurist with a challenge to make modernize the laws. In recent times Muslim academics have adopted a critical approach against the tenets of conservatism in temporal Islam and called them unrepresentative of the true spirit of the Sharia. The present turmoil in the Arab countries has raised the question of legitimacy and the need arises to evaluate the principles of the Compact of Medina, which was proclaimed by the first Islamic state, and secondly, to enquire if the adoption of Sharia can be made contingent upon a consensus of popular sovereignty in order to make it binding in a contract between the ruler and the governed.